Breast Reconstruction: A Century of Controversies and Progress. Issue 4 (April 2018) - Homsy, Antoine; Rüegg, Eva; Montandon, Denys; Vlastos, Georges; Modarressi, Ali; Pittet, Brigitte
Abstract : Abstract: Breast cancer treatment has dramatically changed over the past century. Since Halsted's first description of radical mastectomy in 1882, breast reconstruction has evolved slowly from being considered as a useless or even dangerous procedure by surgeons to the possibility nowadays of reconstructing almost any kind of defect. In this review on the development of breast reconstruction, we outline the historical milestone innovations that led to the current management of the mastectomy defect in an attempt to understand the economic, social and psychological factors, which contributed to slow down its acceptance for several decades.